Comparing forest structures in the border areas of the demilitarized zone of South Korea - Seo, Yeongwan; Lee, Daesung; Cha, Dusong; Choi, Jungkee (Forest science and technology, 2017)
This study was conducted to inventory forest structures focusing on the border areas of the demilitarized zone, which are Goseong, Inje, Yanggu, Hwacheon, Cheolwon, Yeoncheon, and Paju, in South Korea. A total of 707 points were inventoried using a point sampling method. Forest type, tree species, diameter at breast height (DBH), and stand volume per hectare were analyzed and compared. The broad-leaved had the highest frequency with an average of 88%, followed by mixed (7%) and coniferous (5%) forest types in the border areas. A total of 62 tree species were observed and Quercus mongolica had the highest frequency with an average of 28%. By DBH class, small had the highest percentage with 63%, medium was 30%, and large was 7%. Mean DBH was relatively low (16.1 cm) with a range of 13.2 cm to 20.3 cm and the mean stand volume was 107 m 3 ha −1 with a range of 80 m 3 ha −1 to 123 m 3 ha −1 . Compared to the stand volume (137 m 3 ha −1 in average) of the administrative district of the Korea Forest Service, our results showed that the stand volume of the border area is relatively low.